Sistem Informasi Pelaporan Fasilitas Umum Rusak Berbasis Web Terintegrasi GPS di Desa Soso - Nirvana Ivanta Phalosa Jaya; Muhammad Aziz; Mohammad Yusuf Jamil Al-Karim (STMIK PPKIA Pradnya Paramita, 2026)
The development of information technology provides opportunities to improve the quality of public services, including the management of public facilities at the village level. One common problem is the delay in information regarding damaged public facilities because the reporting process is still carried out manually. This study aims to design and develop a web-based information system for reporting damaged public facilities integrated with Global Positioning System (GPS) technology in Soso Village, Gandusari District, Blitar Regency. The research method used is a system development method that includes the stages of requirements analysis, system design, implementation, and system testing. The developed system allows the community to report damaged facilities such as roads, street lighting, and drainage through an online platform using internet-connected devices. The integration of GPS technology enables the system to automatically determine the location of the damage so that officers can easily identify the exact point of the problem in the field. The results of the study indicate that the web-based reporting system can facilitate the community in submitting reports and assist the village government in managing report data in a more structured manner. Therefore, the system helps improve the efficiency, transparency, and effectiveness of public service delivery.